Mutations of Arabidopsis in potential transduction and response components of the phototropic signaling pathway. - Liscum, E (1996)
Four genetic loci were recently identified by mutations that affect phototropism in Arabidopsis thaliana (L.) Heyhn. seedlings. It was hypothesized that one of these loci, NPH1, encodes the apoprotein for a phototropic photoreceptor. All of the alleles at the other three mutant loci (nph2, nph3, and nph4) contained wild-type levels of the putative NPH1 protein and exhibited normal blue-light-dependent phosphorylation of the NPH1 protein. This indicated that the NPH2, NPH3, and NPH4 proteins likely function downstream of NPH1 photoactivation. We show here that, although the nph2, nph3, and nph4 mutants are all altered with respect to their phototropic responses, only the nph4 mutants are also altered in their gravitropic responsiveness. Thus, NPH2 and NPH3 appear to act as signal carriers in a phototropism-specific pathway, whereas NPH4 is required for both phototropism and gravitropism and thus may function directly in the differential growth response. Despite their altered phototropic responses in blue and green light as etiolated seedlings, the nph2 and nph4 mutants exhibited less dramatic mutant phenotypes as de-etiolated seedlings and when etiolated seedlings were irradiated with unilateral ultraviolet-A (UV-A) light. Examination of the phototropic responses of a mutant deficient in biologically active phytochromes, hy1-100, indicated that phytochrome transformation by UV-A light mediates an increase in phototropic responsiveness, accounting for the greater phototropic curvature of the nph2 and nph4 mutants to UV-A light than to blue light.